Shift in herders' territorialities from regional to local scale: the political ecology of pastoral herding in western Burkina Faso - Gonin, A.; Gautier, D. (Springer, 2015)
In Burkina Faso, livestock sedentarization programmes are still at the top of policy makers’ agendas and at the heart of their discourse, despite huge changes in land cover, land use and territorialities in rural areas. This paper contributes to the literature on the impact of livestock policies targeting the sedentarization of pastoralism in sub-Saharan Africa by specifically highlighting the territorial consequences of such policies. This paper suggests that policies directed at improving livestock governance in a context of climate change and changes in land cover and land tenure need to focus on securing pastoralists’ reticular territories, which are made up of corridors and numerous areas of pastureland, rather than on creating disconnected state ranches.